The Role of Apron Movement Control in Aircraft Parking Arrangements at El Tari Kupang Airport Parking Stand - Rahelina Bheku; Suprapti Suprapti (CV. Rayyan Dwi Bharata, 2023)
Apron Movement Control (AMC) is a work unit that has the task and function of regulating and supervising order, safety, smoothness, and allocating parking stands or placing aircraft parking in the apron area. This study aims to find out how the role of AMC officers in arranging aircraft parking at the parking stand and find out what obstacles AMC officers face in arranging aircraft parking at the parking stand at El Tari Kupang Airport. This type of research is qualitative research. To obtain the results of this study using primary data sources and secondary data. Primary data are obtained directly by researchers through interviews, conservation. While secondary data is data obtained indirectly through documentation or activity report documents. After obtaining the necessary data, researchers will process the data into a discussion and make a conclusion and suggestion.Based on the results of research obtained by researchers that in flight operational activities AMC officers have a very important role in arranging aircraft parking at the parking stand because the security, smoothness and safety of aircraft in the apron area are the responsibility of AMC officers. To carry out duties and responsibilities in arranging aircraft parking at the parking stand, AMC officers must carry out in accordance with the applicable Standard Operating Procedure (SOP) in order to avoid the occurrence of something undesirable. And at Kupang El Tari Airport, there were obstacles experienced by AMC officers in carrying out their duties. So it needs to be considered so as not to interfere with flight operational activities, especially in arranging aircraft parking at the parking stand.